2012
DOI: 10.1016/j.jvs.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of a traumatic arteriovenous fistula involving the iliac bifurcation using an iliac branch device

Abstract: Endovascular techniques have shown to be useful in the management of vascular injuries because they transform a complex and potentially dangerous procedure into a safe one. We present the case of a 39-year-old man with congestive heart failure and abdominal bruit 11 years after an abdominal gunshot wound. Imaging studies revealed an arteriovenous fistula involving the left iliac artery bifurcation, and an iliac branch device was used to treat it. Symptoms resolved, and follow-up imaging showed patency of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Fistulae may not be diagnosed immediately and some patients present signs or symptoms years later. 3 In the case described here, the probable cause of AVF was an iatrogenic injury sustained during a laparoscopy procedure five years previously that was not diagnosed at that time. Penetrating traumas, including iatrogenic injuries, are responsible for 20% of AVF.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Fistulae may not be diagnosed immediately and some patients present signs or symptoms years later. 3 In the case described here, the probable cause of AVF was an iatrogenic injury sustained during a laparoscopy procedure five years previously that was not diagnosed at that time. Penetrating traumas, including iatrogenic injuries, are responsible for 20% of AVF.…”
Section: Discussionmentioning
confidence: 82%
“…8 Large collateral vessels with complex venous anatomy often involve significant blood loss. 3 Brewster et al 9 have reported an operative mortality rate for correction of iliac AVF of 5 to 10%. Davis et al 2 documented morbidity of 39% in surgical corrections of iliac AVF.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated venous pressure and surrounding tissue inflammation make the local area hostile for open surgical repair. Large collateral vessels with a complex venous anatomy are often encountered, increased risk for substantial blood loss and high morbidity and mortality [2]. Depending on the diameter of the vein, ligation can be used as also ligation-excision followed by complex reconstruction [4].…”
Section: Referencesmentioning
confidence: 99%
“…If the patient survives, these lesions often not be diagnosed on first evaluation and patients may present with clinical signs and symptoms years later. Open surgical repair can have prohibitive morbidity and mortality and endovascular techniques, an effective alternative, can interrupt the abnormal vascular communication and preserve artery vein patency [2]. We describe a unique case of iliac arteriovenous fistula (AVF), secondary to a bullet injury, identified by imaging studies and subsequently treated with endovascular intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Distal pulses are usually palpable; however a large AV fistula may shunt away blood from the extremity, causing peripheral ischemia. [3] The Nicoladoni-Israel-Branham's sign may be also positive which means manual compression of the AV fistula causes reduced heart rate. [4] The treatment of acquired AV fistulas is primarily surgical.…”
mentioning
confidence: 99%